Problematizing diversity in American education: language and curriculum as catalysts for change - Huseman, Nathan Lee, author; Coke, Pamela K., advisor; Reid, Louann, committee member; Lucero, Rodrick S., committee member (Colorado State University. Libraries, 2011)
Diversity in American education is problematic. The language that both defines and exemplifies diversity is unclear, which produces competing definitions of diversity. As a result, diversity in American education is constructed as a composite of differences between student groups, which include: race, class, language, socio-economic status, and [homo] sexuality. The language, then, promotes pacification with education in the form of sloganizing and tolerance. In addition, diversified curricular pursuits focus on further pacification in the form of recognition and hospitality. For these reasons, I argue that education must move away from diversity as a concept within education, and move toward an inclusive model of education. In order to do so, American education must look at constructing a model based on dialogue and equality, action and transformation. I further argue that language and curriculum are the catalysts for change, and offer possibilities for change within education related to each.
Keywords: American education; tolerance; pacification; diversity